EXPLOSION TEETH BOX PROMOTION MEDIA MODEL AGAINST CHANGES IN TEETH BRUSHING BEHAVIOR IN SCHOOL STUDENTS - Melani Agis Marludia; Masrifan Djamil; Rasipin Rasipin; Suharyo Hadisaputro; Bedjo Santoso (Journal of Applied Health Management and Technology, 2021)
Background: Dental and oral health problems in primary school students are in the high category, this is because efforts to improve dental health behavior of school children are still not optimal. One effective prevention of these problems through the act of brushing your teeth diligently, thoroughly and regularly. Proper dental health education is given to primary school students in the form of media that is packaged by learning while playing. Media promotion explosion teeth box is expected to change the behavior of brushing your child's teeth. Objective: To produce a suitable and effective explosion teeth box promotion media model towards changing tooth brushing behavior among  primary school students. Methods: Research and Development (RD) and product/model trials (quasy experimental control group pretest and posttest design studies). The subjects of class III primary school students were divided into 2 groups: explosion teeth box as an intervention group and flashcard media as a control group and the duration of treatment for 10 days. The results of the model design were validated by experts. Data were tested using the interclass correlation coefficient test, shapiro-wilk, friedman, and post-hoc wilcoxon. Results: The average validation of explosion teeth box experts was 86.66 (very feasible) as a medium for the promotion of dental health in primary school students shown by the p-value (0.001). This model was effective in increasing the knowledge of brushing teeth (p=0.001) and decreasing the index debris score (p=0.001) compared to the control group. Conclusion: The application of explosion teeth box which was carried out for 10 days effectively improved the knowledge of brushing teeth in primary school students compared to the control group. Keywords: Primary school students, explosion teeth box, changing tooth brushing